Effect of styrene-isopren-styrene addition on the recycled polycarbonate/acrylonitrile-butadiene-styrene polymer blends - TAŞDEMİR, MÜNİR (WILEY, 2006)
Interfacial agents as compatibilizers have recently been introduced into polymer blends to improve microstructure and mechanical properties of thermoplastics. In this way, it is possible to prepare a mixture of polymeric materials that can have superior mechanical properties over a wide temperature range. In this study, an incompatible blend of Polycarbonate (PC) and Acrylonitrile Butadiene Styrene (ABS) Copolymer were made compatible by addition of 5, 10, and 20% Styrene-Isopren-Styrene Copolymer (SIS). The mixing operation was conducted using a twin-screw extruder. The morphology and the compatibility of the mixtures were examined by SEM and DSC techniques. Furthermore, the elastic modulus, tensile and yield strengths, percentage elongation, hardness, melt flow index, Izod impact resistance, heat deflection temperature (HDT), Vicat softening point values of polymer alloys of various ratios were determined. It was found that addition of SIS to the structures decreased the tensile strength, yield strength, elastic modulus, and hardness, whereas it increased Izod impact strength and percentage elongation values. (c) 2006 Wiley Periodicals, Inc.
Keywords: polymer alloys; compatibilization; mixture; polycarbonate